Creative Thinking Portrayed on Aladin’s Caharacters - Nurmala Dewi; Evi Yuli Yanti (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2021)
Introducing creative thinking through the movie will be a great way because movies such as Aladdin can be enjoyed by everyone from a wide range of ages. Making the concept of creative thinking will be familiar not only for adults, but also the important thing for children who have been growing up in the process of their lives. By analyzing this movie, the writer aimed to figure out the kinds of creative thinking and its impact on the main characters in Aladin’s movie. The writer applied the Descriptive Qualitative method to obtain and represent the data. The process of collecting data by doing library research, reading some theories to support the analysis, watching the movie as the object of the research. After analysis, it found the kinds of creative thinking in the main characters of Aladdin are only three out of four categories; they are reframing, mind mapping, and insight. Besides, the impact of creative thinking reflected are increase confidence and arise diverse thinking which generating innovative ideas to solve the problem and give benefit to the individual and the community.